Polycladia myrica-based delivery of selenium nanoparticles in combination with radiotherapy induces potent in vitro antiviral and in vivo anticancer activities against Ehrlich ascites tumor - Abo-Neima, Sahar E.; Ahmed, Abdelhamid A.; El-Sheekh, Mostafa; Makhlof, Mofida E. M. (Frontiers in Molecular Biosciences, 2023)
Background: Over the last few decades, nanotechnology has entered daily life through various applications, therefore, there has been a trend toward developing new approaches to green-mediated nanotechnology that encourage nanomaterial formation through biological methods such as plants or microorganisms. Algae have gained increasing attention from nanotechnology scientists and have paved the way for the emergence of “algae nanotechnology” as a promising field. Methods: Via using the aqueous extract of the brown alga Polycladia myrica, selenium nanoparticles were synthesized and characterized by using seven instruments: SEM, TEM, UV spectra, Zeta potential, EDX, X-ray diffraction, and FTIR. P. myrica selenium nanoparticles (PoSeNPs) were then examined for their antiviral activity against HSV-1 (Herpes simplex I) and anticancer against human colon cancer cell line (HCT-116) in vitro and in vivo alone and in combination with laser therapy of power 2 mW against Ehrlich carcinoma (EAC). Results: PoSeNPs ranging between 17.48 nm and 23.01 nm in size, and EDX revealed the selenium mass and its atoms as 0.46% ± 0.07% and 0.08% ± 0.01% respectively. Their anticancer potentiality in vitro was with maximum inhibitions of 80.57% and 73% and IC50 = 14.86 μg/mL and 50 mg/mL against HCT-116 and EAC cell lines respectively, while their in vivo alone and in combination with laser therapy of power 2 mW showed a potent therapy effect against Ehrlich ascites carcinoma (EAC). Conclusion: This study concluded that PoSeNPs do not have a toxic effect; they exhibit high effectiveness as a photothermal agent for cancer therapy, with promising applications in future biomedical fields. The combined therapy showed a significant decrease in tumor volume, massive tumor cell necrosis, shrinking, and disappearance. It also showed improvement in liver TEM, histology, kidney function: urea and creatinine, and liver enzymes: ALT, and AST.